2019
DOI: 10.1002/nop2.274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intradialytic resistance exercises on physical performance, nutrient intake and quality of life among haemodialysis people: A systematic review and meta‐analysis

Abstract: Objectives The aim of this systematic reviews was to synthesize the current studies for the effectiveness of intradialytic resistance exercises with usual care on HD people. Design Meta‐analysis of randomized controlled studies. Methods A systematic search of seven electronic databases, including PubMed, EMBASE, the Cochrane Library, Web of Science, WanFang, China National Knowledge Infrastructure (CNKI) and SINOMED, was systematically search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
2
19
0
1
Order By: Relevance
“…Results also showed that the intradialytic group exercise could improve the QOL of MHD patients gradually. This nding was in consistence with what were found before [53][54][55][56]. Survival of MHD patients has been prolonged, but the improvement in quality of life has not keep in pace obviously [57].…”
Section: Discussionsupporting
confidence: 88%
“…Results also showed that the intradialytic group exercise could improve the QOL of MHD patients gradually. This nding was in consistence with what were found before [53][54][55][56]. Survival of MHD patients has been prolonged, but the improvement in quality of life has not keep in pace obviously [57].…”
Section: Discussionsupporting
confidence: 88%
“…The search identified 2305 potential articles, of which 648 were duplicates. After reading the title and abstract, 1598 papers were excluded and 28 were excluded after full-text review resulting in 31 final studies 10 24–53. The PRISMA flow chart of study inclusion is illustrated in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of exercise on the 6 min walk test was investigated in 14 meta-analyses (reported in 13 articles) with a mild heterogeneity (average I 2 =44.9%),25 28–30 32 34 36–38 40 41 43 51 and 13 reported positive statistically significant outcomes 25 28–30 32 34 36–38 41 43 51. Of the 14 meta-analyses, 2 reported a small effect size,25 28 5 reported a moderate effect size36 37 41 43 51 and 3 reported a large effect size 32 34 38. GRADE assessment of quality indicated the overall evidence as being very low (eight meta-analyses25 30 32 34 38 40 43), low (four meta-analyses28 37 41 51) and moderate (two meta-analyses29 36).…”
Section: Resultsmentioning
confidence: 99%
“…A significant increase in pre-albumin was observed after resistance training compared to non-active patients [ 77 ]. Chan et al [ 78 ] and Zhang et al [ 79 ] found preliminary evidence that resistance training can reduce malnutrition and no significant improvement in nutrient intake, respectively.…”
Section: Discussionmentioning
confidence: 99%